THE ROLE OF CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), AND TOTAL ASSET TURNOVER (TATO) ON RETURN ON ASSET (ROA) IN MULTI-INDUSTRIAL SECTOR MANUFACTURING COMPANIES THAT REGISTERED TO THE INDONESIA STOCK EXCHANGE FOR 2015-2019 - Damayanti, Ellya; Chaerudin, Chaerudin (Dinasti Publisher, 2021)
The research intention was to investigate further relates to the impact caused by Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) to Return on Assets (ROA) in Manufacturing Companies in the Multi-Industrial Sector which registered on the Indonesia Stock Exchange during 2015 -2019. This research were used a descriptive verification method and secondary data to be processed. The sampling technique used was purposive sampling with total sample of 9 companies. Research approach which applied here was multiple regression analysis method. And it has the result which indicate that the role of CR, DER, and TATO on ROA was simultaneously significant of 34.4%. However, there has partially impact which only occured on CR and TATO to ROA.